Targeting coagulation factor XII as a novel therapeutic option in brain trauma. Issue 6 (28th April 2016) - Hopp, Sarah; Albert‐Weissenberger, Christiane; Mencl, Stine; Bieber, Michael; Schuhmann, Michael K.; Stetter, Christian; Nieswandt, Bernhard; Schmidt, Peter M.; Monoranu, Camelia‐Maria; Alafuzoff, Irina; Marklund, Niklas; Nolte, Marc W.; et al.
Abstract : Objective: Traumatic brain injury is a major global public health problem for which specific therapeutic interventions are lacking. There is, therefore, a pressing need to identify innovative pathomechanism‐based effective therapies for this condition. Thrombus formation in the cerebral microcirculation has been proposed to contribute to secondary brain damage by causing pericontusional ischemia, but previous studies have failed to harness this finding for therapeutic use. The aim of this study was to obtain preclinical evidence supporting the hypothesis that targeting factor XII prevents thrombus formation and has a beneficial effect on outcome after traumatic brain injury. Methods: We investigated the impact of genetic deficiency of factor XII and acute inhibition of activated factor XII with a single bolus injection of recombinant human albumin‐fused infestin‐4 (rHA‐Infestin‐4) on trauma‐induced microvascular thrombus formation and the subsequent outcome in 2 mouse models of traumatic brain injury. Results: Our study showed that both genetic deficiency of factor XII and an inhibition of activated factor XII in mice minimize trauma‐induced microvascular thrombus formation and improve outcome, as reflected by better motor function, reduced brain lesion volume, and diminished neurodegeneration. Administration of human factor XII in factor XII–deficient mice fully restored injury‐induced microvascular thrombus formation and brain damage. Interpretation: The robust protective effect of rHA‐Infestin‐4 points to a novel treatment option that can decrease ischemic injury after traumatic brain injury without increasing bleeding tendencies. Ann Neurol 2016;79:970–982